2014
DOI: 10.1177/2156869314532376
|View full text |Cite
|
Sign up to set email alerts
|

Disability, Health Insurance, and Psychological Distress among US Adults

Abstract: Structural resources, including access to health insurance, are understudied in relation to the stress process. Disability increases the likelihood of mental health problems, but health insurance may moderate this relationship. We explore health insurance coverage as a moderator of the relationship between disability and psychological distress. A pooled sample from 2008–2010 (N=57,958) was obtained from the Integrated Health Interview Series. Chow tests were performed to assess insurance group differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Disability and mental health scholarship has demonstrated that the comparably greater prevalence of depression or depressive symptoms among people with disabilities derives substantially from social marginalization and differential exposure to social stressors ( Alang, McAlpine, and Henning-Smith 2014 ; Brown and Turner 2010 ; Turner, Lloyd, and Taylor 2006 ). This is supported within the COVID-19 context by research demonstrating that people with disabilities have been more likely than people without disabilities to experience difficulties at work; at home; in personal, family, and social relationships; and related to health and health care access ( Ciciurkaite et al 2022 ; Landes et al 2020 ; Okoro et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disability and mental health scholarship has demonstrated that the comparably greater prevalence of depression or depressive symptoms among people with disabilities derives substantially from social marginalization and differential exposure to social stressors ( Alang, McAlpine, and Henning-Smith 2014 ; Brown and Turner 2010 ; Turner, Lloyd, and Taylor 2006 ). This is supported within the COVID-19 context by research demonstrating that people with disabilities have been more likely than people without disabilities to experience difficulties at work; at home; in personal, family, and social relationships; and related to health and health care access ( Ciciurkaite et al 2022 ; Landes et al 2020 ; Okoro et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of physical disability and functional limitation in the population raise concern because of their association with a host of secondary physical and mental health complaints, the most prevalent of which is depressive symptoms (Alang, McAlpine, & Henning-Smith, 2014; Hughes, Swedlund, Petersen, & Nosek, 2001; Nosek & Hughes, 2003). For example, people with physical disabilities are found to experience as much as three times the number of depressive symptoms as does the general population (Mirowsky & Ross, 1999), and greater functional limitation is associated with greater depressive symptoms both cross-sectionally and over time (Breslin, Gnam, Franche, Mustard, & Lin, 2006; Caputo & Simon, 2013; Yang, 2006).…”
mentioning
confidence: 99%
“…As of February 2021, 12 states have not adopted the Medicaid expansion as part of the ACA [ 54 ]. Some states which have not participated, such as Texas, has the highest rate of uninsured in the country [ 55 ]. Policy options could consider expanding subsidies or other affordable coverage options to targeted populations including long-term uninsured adults with multiple chronic health conditions.…”
Section: Discussionmentioning
confidence: 99%